An analytical model of diesel injector's needle valve eccentric motion. (March 2022) - Wang, Chuqiao; Adams, Moro; Jin, Tianyu; sun, Yu; Röll, Andreas; Luo, Fuqiang; Gavaises, Manolis
Past experimental studies have shown that the needle valve of high-pressure diesel injectors undergoes lateral movement and deformation, while the continuous increase in injection pressure enlarges the gap of the needle valve assembly. Two different analytical models, considering or omitting this change are presented here, linking the geometries of the needle valve assembly with the magnitude of needle valve tip lateral movement. It is found that the physical dimensions of the needle valve assembly and the injection pressure have a significant impact on the radial displacement of the needle. For example, for nominal clearances between the needle guidance and the needle valve of about 1–3 μm, the magnitude of the radial movement of the needle tip could reach tens of microns. The model that takes into account the variation of the gap between the needle guide and needle valve is found to give predictions closer to the experimental results.